Pembuatan perangkat pembelajaran ipa terpadu berbasis model creative problem solving pada materi getaran, gelombang, dan bunyi IPA SMP/MTs kelas VIII - Rizka Okta Perrina; Yurnetti Yurnetti; Hidayati Hidayati; Silvi Yulia Sari (Universitas Negeri Padang, 2020)
Learning Devices are devices used in the learning process. Learning tools must be able to assist students in forming competencies and character. Based on the observation of learning devices at this time can not help students in forming competencies and character well . In addition, the student activity in the learning process is still passive. Therefore, learning tools are developed that can support the achievement of students' competencies and character. The purpose of this study is to develop Integrated Science learningmedia like lesson plans along with student worksheet based on Creative Problem Solving models with valid and practical criteria. The type of this research is Research and Development (R&D). The R&D research method used to produce certain products. The subject were students of SMPN 33 Padang grade VIII which registrated in 2019/2020 academic year and two science teachers. Based on the result of this study, the validity of this product is 80,92% with a valid of category, the practicality according to the teacher is 83,71% with very practical category, and the practicality according to the students is 84,72% with a very practical category.